Implementation of the A+ schools program: An examination of baseline teacher perceptions and instructional behaviors - Miller, Rachelle; Wake, Donna; Whittingham, Jeff L. (Journal of Interdisciplinary Studies in Education, 2016)
In a baseline study of teachers’ attitudes towards arts integration, elementary teachers (23 experimental; 23 control) in grades K-6 indicated they valued arts integration and were willing to integrate the arts in their classrooms with no significant differences between groups. Additional analysis of teachers’ instructional behaviors with structured protocols prior to program implementation showed that teachers from the control school demonstrated significantly higher uses of interdisciplinary curricula planning, experiential learning, and critical thinking. These data indicate that schools choosing to adopt an arts integrated curricula may be predisposed to the concepts underlying effective arts integration; they may also recognize their need for support in implementing arts integrated curricula via structured program implementation and suppor